2016
DOI: 10.1007/s10815-016-0715-3
|View full text |Cite
|
Sign up to set email alerts
|

A new mutation identified in SPATA16 in two globozoospermic patients

Abstract: The present study confirms the pathogenicity of the SPATA16 mutations. The fact that no variation was detected in the coding sequence of AFGF1, GOPC, PICK1 and IRGC does not mean that they are not involved in human globozoospermia. A larger globozoospermic cohort must be studied in order to accelerate the process of identifying new genes involved in such phenotypes. Until sufficient numbers of patients have been screened, AFGF1, GOPC, PICK1 and IRGC should still be considered as candidate genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 14 publications
0
44
0
Order By: Relevance
“…In our previous studies, we have demonstrated firstly that the DPY19L2 alteration was the major cause of this syndrome in a large cohort of Tunisian globozoospermic patients (Ghedir et al, ). More recently, we have identified a new rare mutation in SPATA16 in two unrelated Tunisian patients (ElInati et al, ). In fact, it consists in a deletion of 22.6 Kb encompassing the exon 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we have demonstrated firstly that the DPY19L2 alteration was the major cause of this syndrome in a large cohort of Tunisian globozoospermic patients (Ghedir et al, ). More recently, we have identified a new rare mutation in SPATA16 in two unrelated Tunisian patients (ElInati et al, ). In fact, it consists in a deletion of 22.6 Kb encompassing the exon 2.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation screening for DPY19L2 and SPATA16 was then performed by PCR and Sanger sequencing of the exons and intronic flanking sequences of these genes. Primer sequences and PCR conditions are as described previously (ElInati et al, ; Ghedir et al, ) and listed in the supplementary data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…176 Some obvious structural defects can be detected microscopically, whereas some defects in energy production, signalling transduction and metabolism require more sophisticated assays for screening. Although the molecular diagnosis of infertility would be difficult with the current available technologies, we suggest that deletions and/or mutations in SPATA16 , 36, 37 PICK1 , 38 DPY19L2 , 39 ZPBP1 , 40 DNAH1 , 41 CatSper1 / 2 , 143, 144, 145 GALNTL5 158 and others 7 need to be checked for infertility diagnosis of globozoospermia. Whole genome-based techniques will hopefully help to identify more infertility-related mutations and risk factors in future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Among them, deletions and/or mutations in SPATA16 , 36, 37 PICK1 , 38 DPY19L2 , 39 ZPBP1 40 and DNAH1 41 have been identified in globozoospermia patients. The involvement of the human orthologues of the other above-mentioned mouse genes in human globozoospermia requires further investigation.…”
Section: Globozoospermia-related Proteins: Roles In Acrosomementioning
confidence: 99%